Detection of Microbial Agents in Oropharyngeal and Nasopharyngeal Samples of SARS-CoV-2 Patients - Seckar, Tyler; Lin, Xiang; Bose, Dipayan; Wei, Zhi; Rohrbaugh, Joseph; Collman, Ronald G.; Robertson, Erle S. (Frontiers in Microbiology, 2021)
The novel coronavirus outbreak started in December 2019 and rapidly spread around the globe, leading to a global pandemic. Here we reported the association of microbial agents identified in oropharyngeal and nasopharyngeal samples from patients with SARS-CoV-2 infection, using a Pan-microarray based technology referred to as PathoChIP. To validate the efficiency of PathoChIP, reference viral genomes obtained from BEI resource and 25 SARS-CoV-2 positive clinical samples were tested. This technology successfully detected femtogram levels of SARS-CoV-2 viral RNA, which demonstrated greater sensitivity and specificity than conventional diagnostic techniques. Simultaneously, a broad range of other microorganisms, including other viruses, bacteria, fungi and parasites can be detected in those samples. We identified 7 viral, 12 bacterial and 6 fungal agents common across all clinical samples suggesting an associated microbial signature in individuals who are infected with SARS-CoV-2. This technology is robust and has a flexible detection methodology that can be employed to detect the presence of all human respiratory pathogens in different sample preparations with precision. It will be important for differentiating the causative agents of respiratory illnesses, including SARS-CoV-2.